2011
DOI: 10.5858/arpa.2010-0731-oa
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Endothelial Cells as a Marker of Vascular Dysfunction in Patients With Systemic Lupus Erythematosus by Real-Time Polymerase Chain Reaction

Abstract: Endothelial dysfunction is present in SLE patients even in the absence of traditional cardiovascular risk factors due to disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…Other potential sources presented included hairs, fibers, stain precipitate, bacteria, endothelial cells, and sporozoan microgametes. Some basic features regarding these additional sources of blood smear contamination were presented, and salient features are found in the attached references: hairs and fibers, 67,68 stain precipitate, 69 bacteria, 70,71 endothelial cells, 72 -74 and sporozoan microgametes. 75 -78 In summary, the take-home message regarding the spores of helicosporous fungi is that they are air-borne or water-based contaminants in laboratories and they may be mistaken for microfilariae in stained blood smears.…”
Section: Blood Smear Contaminantmentioning
confidence: 99%
“…Other potential sources presented included hairs, fibers, stain precipitate, bacteria, endothelial cells, and sporozoan microgametes. Some basic features regarding these additional sources of blood smear contamination were presented, and salient features are found in the attached references: hairs and fibers, 67,68 stain precipitate, 69 bacteria, 70,71 endothelial cells, 72 -74 and sporozoan microgametes. 75 -78 In summary, the take-home message regarding the spores of helicosporous fungi is that they are air-borne or water-based contaminants in laboratories and they may be mistaken for microfilariae in stained blood smears.…”
Section: Blood Smear Contaminantmentioning
confidence: 99%
“…Murine models of lupus showed that NAC treatment suppressed autoantibody formation, reduced nephritis and prolonged survival [72]. Several groups have shown that the decrease in intracellular glutathione has been associated with many clinical features like, nephritis [14], CNS [103], endothelial activation in cardiovascular and cerebrovascular involvement [104] in SLE patients. Administration of NAC has shown beneficial effect in mild SLE patients in terms of decreasing lipid peroxidation, improve CNS complication [103], endothelial function [104,105] in patients with cerebrovascular involvement.…”
Section: Reviewmentioning
confidence: 99%
“…Recently, circulating endothelial cells (CECs) have been established as markers of endothelial damage or dysfunction [9]. CEC levels increase in many kinds of disorders such as cardiovascular [10], [11], autoimmune [12], and infectious diseases [13], as well as in cancer [14]. In cancer patients, CEC number correlates with tumor progression [15] and constitutes a promising tool for monitoring disease activity, with potential for the assessment of prognosis and response to treatment.…”
Section: Introductionmentioning
confidence: 99%